Key concepts in anti-discriminatory social work - Okitikpi, Toyin; Aymer, Cathy (London ; Thousand Oaks, Calif. : SAGE, 2010)
This Key Concepts clearly and concisely explains the basic ideas in the field of anti-discriminatory social work. It explores the range of discriminations that people experience and discusses a number of theori es that inform anti-discriminatory practice ; considers the legal frame works within which anti-discriminatory practice operates; analyses the skills and knowledge required to practice effectively; highlights the d ynamic nature of anti-discriminatory practice and points the way toward s a new practice dimension. Provides an essential reference guide for a ll social work students and practitioners, as well as those taking cour ses in teacher training, youth and community, nursing, mid-wifery and m ental health studies for whom anti-discriminatory practice is an import ant element in their study.
Pt. 1. Underpinning ideas and concepts. -- 1. The nature of discrimi nation -- 2. Ideas informing anti-discriminatory practice models -- 3. Models of anti-discriminatory practice -- 4. The political dimension of anti-discriminatory practice -- 5. Legislation and policies -- Pt. 2. Implementation and practice considerations. -- 6. Working with diversit y and challenging the status quo -- 7. Key skills, knowledge and anti-d iscriminatory practice -- 8. Integrating anti-discriminatory practice i nto social work methods and approaches -- 9. The dynamic nature of anti -discriminatory practice -- 10. Towards a new practice dimension.
Includes bibliographical references (p. 161-166) and index.
Keywords: Social service; Discrimination; Social work with minorities